PERGESERAN PERSEPSI TERHADAP PENDIDIKAN KOMUNITAS ADAT TERPENCIL DI PULAU KUNDUR KABUPATEN KARIMUN PROVINSI KEPULAUAN RIAU - Tika Permata Sari; Kamaruddin Kamaruddin; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Education is a fundamental thing that must be owned by all levels of society in Indonesia. Equitable and affordable education should be felt by all Indonesian people, Especially for the Indigenous communities in Kundur Island Karimun Regency Riau Archipelago Province namely Duano Indigenous Community and Mantang Indigenous Community. This study aims to determine (1) the socioeconomic conditions of Remote Indigenous Community life on Kundur Island (2) shifting perceptions of Remote Indigenous Communities to education (3) the role of education in influencing the life of Remote Indigenous Communities in Kundur Island. This study uses a combination of quantitative and qualitative methods with a sociology approach and using data collection techniques in the form of observation, interviews, and questionnaires. The results of this study indicate that the desire of the parents of indigenous communities in the island of Kundur to send their children to the higher levels but still constrained by several factors that are difficult to pass. The existence of indigenous communities is reported to have existed since the 1940s and today indigenous communities have occupied their precise neighborhoods for generations. Until now, there are still many community members of indigenous communities who do not complete formal education and found many early childhood children who work to help their parents.Keywords: Remote Indigenous Communities, Education